The Effect of Cooperative Learning Two Stay Two Stray on Students Learning Outcomes in Surface Area - Desilia Elisabet; Agung Hartoyo; Yulis Jamiah (Universitas Tanjungpura, 2020)
Â Â The study aimed to determine the influence of Two Stay Two Stray cooperative learning outcomes in surface area concepts. The method used in this study was an experimental method with a quasi-experimental form and the research design was a posttest only control design. The population of this research was 9th-grade students of 18 junior high schools in Pontianak and were divided into five classes. The sample was 9th D and 9th E grade taken using a simple random sampling technique. Data collection techniques used measurement techniques and data collection tools with a description test to determine student learning outcomes. After the data were tested in the two samples, data analysis performed to test the hypothesis. Before testing the hypothesis, the prerequisite test was the normality test. The normality test was not normal then the data analysis used Mann Whitney U-Test. From the data analysis results, obtained z count value of 1,87, while the z table value of 1,64 for ð›¼ = 0.05. Because of the z count > z table, it is concluded that there is an influence of Two Stay Two Stray cooperative learning on student learning outcomes.Â Keywords: Cooperative Learning, Surface Area, Two Stay Two Stray